Liquid crystal material, laminate, optical component, display device, and method for manufacturing the laminate
Patent Information
- Application Number
- JP2023005893
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-01-18
AI Technical Summary
【0009】 本発明によれば、配向膜を用いなくても液晶モノマーが垂直配向可能な液晶材料等を提供することができる。
Smart Images

Figure 0007943823000009 
Figure 0007943823000010 
Figure 0007943823000011
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal material, a laminate, an optical member, a display device, and a method for producing the laminate.
Background Art
[0002] As a conventional technique, Patent Document 1 discloses an optical compensation film having a transparent support and an optically anisotropic layer formed on the transparent support from a liquid crystal composition containing a liquid crystalline compound. In the optically anisotropic layer of this optical compensation film, the liquid crystalline compound having a polymerizable group is vertically aligned.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problem to be Solved by the Invention
[0004] A liquid crystal layer composed of a polymerizable liquid crystal compound in which a liquid crystal monomer is vertically aligned may be used for a retardation film or the like. Examples of the method for vertically aligning the liquid crystal monomer in the liquid crystal layer include a method using an alignment film for vertically aligning the liquid crystal monomer. In this method, an alignment film is formed on a support layer on which the liquid crystal layer is to be laminated, and a liquid crystal material containing the liquid crystal monomer is applied onto the alignment film. However, when the alignment film is formed on the support layer, the adhesion between the liquid crystal layer and the support layer may decrease, or the production process of the retardation film or the like having the liquid crystal layer may become complicated in some cases. An object of the present invention is to provide a liquid crystal material and the like that enable vertical alignment of a liquid crystal monomer without using an alignment film.
Means for Solving the Problem
[0005] The liquid crystal material of the present invention is a liquid crystal material for forming a polymerizable liquid crystal compound, comprising a liquid crystal monomer and an acrylamide monomer Furthermore, the liquid crystal monomer includes at least one first liquid crystal monomer having reactive groups at both ends of the molecule, and at least one second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end. . Here, a silane coupling agent may be further included. In addition, the silane coupling agent may have an amino group. Furthermore, it is possible to ensure that the material does not contain any monomers other than liquid crystal monomers and acrylamide monomers. Furthermore, the liquid crystal monomer may contain a larger amount of the first liquid crystal monomer than the second liquid crystal monomer. Furthermore, when the total amount of the liquid crystal material is taken as 100 parts by mass, the content of the material having an amino group may be 1 part by mass or more and 30 parts by mass or less.
[0006] Furthermore, the laminate of the present invention comprises a support layer, The molecule comprises at least one first liquid crystal monomer having reactive groups at both ends of the molecule, and at least one second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end. and a liquid crystal layer comprising a polymerizable liquid crystal compound that contains a liquid crystal monomer and an acrylamide monomer. Formed by coating a liquid crystal material onto a support layer and polymerizing it. Here, support the support layer may have a contact angle with water of 30° or more and 60° or less. Furthermore, the liquid crystal layer is a positive C plate in which the liquid crystal monomer is vertically aligned, and when the retardation for a wavelength λ (nm) of light in the thickness direction of the liquid crystal layer is denoted as Rth_C(λ), it may satisfy -50 nm < Rth_C(550) < -150 nm. Furthermore, for the support layer, the refractive indices in two directions in the in-plane direction of the support layer are denoted as n x2 and n y2 , support the refractive index in the thickness direction of the support layer is denoted as n z2 , x2 ≧n y2 >n z2 is satisfied. The liquid crystal layer is a positive C plate obtained by crosslinking the liquid crystal monomer in a vertically aligned state, and may be directly laminated on the support layer. Furthermore, for the support layer, when the in-plane retardation for a wavelength λ (nm) of light of the support layer is denoted as Re_A(λ), it may satisfy 10 nm < Re_A(550) < 200 nm. Further, the support layer can be configured to satisfy Re_A(450)<Re_A(550)<Re_A(650), where Re_A(λ) is the retardation for light of wavelength λ (nm) in the in-plane direction of the support layer. Further, the support layer can contain at least one of diacetyl cellulose, triacetyl cellulose, cellulose acetate butyrate, cellulose acetate propionate, cycloolefin, and polycarbonate as the resin. Further, the support layer can contain a plurality of types of resins having different wavelength dispersion characteristics. Further, the support layer can contain a resin and particles. Further, the particles can contain smectite. Further, for the particles, the refractive indices in two directions in the in-plane direction of the support layer are defined as n x3 and n y3 , support and the refractive index in the thickness direction of the support layer is defined as n z3 , the particles can be configured to satisfy n x3 ≧n y3 >n z3 . Further, the particles can be configured to satisfy Rth_P(450)>Rth_P(550)>Rth_P(650), where Rth_P(λ) is the retardation for light of wavelength λ (nm) in the thickness direction of the support layer. Further, the support layer can be configured such that the wavelength dispersion characteristic of retardation in the in-plane direction of the support layer is different from the wavelength dispersion characteristic of retardation in the thickness direction of the support layer. Further, the support layer can be configured to satisfy Re_A(450) / Re_A(550)<Rth_A(450) / Rth_A(550), where Re_A(λ) is the retardation for light of wavelength λ (nm) in the in-plane direction of the support layer, and Rth_A(λ) is the retardation for light of wavelength λ (nm) in the thickness direction of the support layer.
[0007] Furthermore, the optical component of the present invention comprises a polarizing member that polarizes light and a phase difference film laminated on the polarizing member. The laminate comprises a support layer and a liquid crystal layer laminated on the support layer and made of a polymerizable liquid crystal compound containing a liquid crystal monomer and an acrylamide monomer. Here, the support layer of the laminate has a refractive index in two directions in the in-plane direction of the support layer, n x2 and n y2 Let the refractive index in the thickness direction of the support layer be n z2 In that case, n x2 ≥n y2 >n z2 The following conditions are met. Furthermore, when the polarizing member, support layer, and liquid crystal layer are stacked in this order, the absorption axis of the polarizing member and the slow axis of the support layer can be arranged orthogonally. Also, when the polarizing member, liquid crystal layer, and support layer are stacked in this order, the absorption axis of the polarizing member and the slow axis of the support layer can be arranged parallel to each other.
[0008] Furthermore, the display device of the present invention includes a liquid crystal cell that controls the light transmission state and an optical member laminated on the liquid crystal cell. The optical member comprises a polarizing member that polarizes light and a phase difference film made of a laminate laminated on the polarizing member. The laminate comprises a support layer and a liquid crystal layer laminated on the support layer and made of a polymerizable liquid crystal compound containing a liquid crystal monomer and an acrylamide monomer. Furthermore, the display device of the present invention includes an organic EL layer containing an organic EL light-emitting element and an optical element laminated on the organic EL layer. The optical element comprises a polarizing member that polarizes light and a phase difference film made of a laminate laminated on the polarizing member. The laminate comprises a support layer and a liquid crystal layer laminated on the support layer and made of a polymerizable liquid crystal compound containing a liquid crystal monomer and an acrylamide monomer. Here, the angle between the absorption axis of the polarizing member and the slow-phase axis of the support layer can be set to 40° or more and 50° or less. Furthermore, the manufacturing method of the laminate of the present invention involves placing a support layer on top of the support layer. The molecule comprises at least one first liquid crystal monomer having reactive groups at both ends of the molecule, and at least one second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end. Liquid crystal monomer and acrylamide monomer dispersed in the solvent The process of applying liquid crystal material, A process of vertically aligning liquid crystal monomers by evaporating a solvent from the liquid crystal material,The process includes polymerizing a liquid crystal material to form a liquid crystal layer consisting of a polymerizable liquid crystal compound in which liquid crystal monomers are vertically oriented. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide a liquid crystal material, etc., in which liquid crystal monomers can be vertically aligned without using an alignment film. [Brief explanation of the drawing]
[0010] [Figure 1] This diagram illustrates a phase difference film to which this embodiment is applied. [Figure 2] This diagram illustrates the orientation state of the liquid crystal layer in a phase difference film. [Figure 3] This is a diagram illustrating other forms of the supporting layer. [Figure 4] This figure illustrates an example of a method for manufacturing a phase difference film according to this embodiment. [Figure 5] This diagram illustrates a liquid crystal display device to which the phase difference film of this embodiment is applied. [Figure 6] This figure illustrates an organic EL display device 2 to which the phase difference film of this embodiment is applied. [Figure 7] Figures (a) and (b) show the measurement results of the brightness of a liquid crystal display device. [Figure 8] Figures (a) and (b) show the measurement results of the brightness of a liquid crystal display device. [Modes for carrying out the invention]
[0011] The embodiments for carrying out the present invention will be described in detail below. However, the present invention is not limited to the embodiments described below. Furthermore, the present invention can be implemented in various modifications within the scope of its gist. In addition, the drawings used below are for illustrating embodiments of the present invention and do not represent actual sizes.
[0012] <Explanation of Phase Difference Film 10> Figure 1 is a diagram illustrating a phase difference film 10 to which this embodiment is applied, and shows an example of the cross-sectional structure of the phase difference film 10. Figure 2 is a diagram illustrating the orientation state of the liquid crystal layer 11 of the phase difference film 10, which will be described later. As will be described in detail later, the phase difference film 10 of this embodiment is used by being attached to a display device such as a liquid crystal panel or an organic EL panel. By using the phase difference film 10, effects such as improved viewing angle characteristics and suppression of external light reflection in the display device can be obtained.
[0013] The phase difference film 10 is an example of a laminate and comprises a liquid crystal layer 11 made of a polymerizable liquid crystal compound and a support layer 12 on which the liquid crystal layer 11 is laminated. In the phase difference film 10 of this embodiment, the liquid crystal layer 11 is laminated directly on the support layer 12 without the interposition of other layers such as an alignment film.
[0014] (Liquid crystal layer 11) The liquid crystal layer 11 is composed of a polymerizable liquid crystal compound containing liquid crystal monomers. The liquid crystal layer 11 in this embodiment is a so-called positive C plate, and as shown in Figure 2, the liquid crystal monomers are vertically oriented (homeotropically oriented). In addition, in the liquid crystal layer 11, the orientation state of the liquid crystal monomers is fixed so that the orientation direction faces vertically through polymerization. The liquid crystal layer 11 of this embodiment includes a liquid crystal monomer and an acrylamide monomer.
[0015] The liquid crystal layer 11 contains a liquid crystal monomer having a reactive group within its molecule. A reactive group is a group that undergoes a polymerization reaction upon irradiation with active radiation such as visible light, ultraviolet light, X-rays, electron beams, alpha rays, beta rays, and gamma rays. The reactive groups of the liquid crystal monomer are not particularly limited, but examples include vinyl groups, acrylic groups, methacrylic groups, epoxy groups, and styryl groups. These reactive groups may have substituents. When a liquid crystal monomer has a reactive group within its molecule, the polymerization of the liquid crystal monomer by the reactive group makes it easier to fix the orientation state of the vertically oriented liquid crystal monomer in the liquid crystal layer 11. As a result, the orientation state of the liquid crystal layer 11 is less likely to change over time, improving the reliability of the phase difference film 10.
[0016] The liquid crystal layer 11 preferably contains both a first liquid crystal monomer having reactive groups at both ends of the molecule and a second liquid crystal monomer having a reactive group at one end and a cyano group at the other end, as liquid crystal monomers having reactive groups within the molecule. The first liquid crystal monomer having reactive groups at both ends of the molecule may be a single type of liquid crystal monomer or a combination of multiple types of liquid crystal monomers. Similarly, the second liquid crystal monomer having a reactive group at one end and a cyano group at the other end may be a single type of liquid crystal monomer or a combination of multiple types of liquid crystal monomers.
[0017] Examples of first liquid crystal monomers having reactive groups at both ends of the molecule include the liquid crystal monomers represented by the following formulas (1) to (9).
[0018] [ka]
[0019] Furthermore, as a second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end, examples include the liquid crystal monomers of the following formulas (10) to (13).
[0020] [ka]
[0021] The liquid crystal layer 11 preferably contains a large amount of the first liquid crystal monomer, which has a reactive group at one end of the molecule and a cyano group at the other end of the molecule, compared with the second liquid crystal monomer, which has a reactive group at one end of the molecule and a cyano group at the other end of the molecule. Note that the liquid crystal layer 11 containing a large amount of the first liquid crystal monomer compared with the second liquid crystal monomer means that the number of structures derived from the first liquid crystal monomer is greater than the number of structures derived from the second liquid crystal monomer contained in the liquid crystal layer 11. The liquid crystal layer 11 contains more of the first liquid crystal monomer than the second liquid crystal monomer, which makes it easier for the liquid crystal monomers to polymerize with each other. As a result, the orientation state of the vertically oriented liquid crystal monomers in the liquid crystal layer 11 is more easily fixed, and the reliability of the phase difference film 10 is further improved.
[0022] Furthermore, in addition to the first and second liquid crystal monomers described above, the liquid crystal layer 11 may also contain other liquid crystal monomers having a reactive group at one end of the molecule. Other examples of liquid crystal monomers include those represented by the following equations (14) to (18).
[0023] [ka]
[0024] The liquid crystal monomer content in the liquid crystal layer 11 is preferably 50 parts by mass or more and 95 parts by mass or less, and more preferably 70 parts by mass or more and 90 parts by mass or less, when the total polymerizable liquid crystal compound constituting the liquid crystal layer 11 is 100 parts by mass. If the liquid crystal monomer content is less than 50 parts by mass, the amount of liquid crystal monomer contained in the liquid crystal layer 11 is small, which may make it difficult to polarize the light incident on the liquid crystal layer 11. When the liquid crystal monomer content exceeds 95 parts by mass, the orientation of the liquid crystal material tends to deteriorate, making it difficult to achieve vertical orientation.
[0025] Furthermore, the liquid crystal layer 11 contains an acrylamide monomer represented by the following formula (18).
[0026] [ka]
[0027] In this embodiment, the liquid crystal layer 11 contains an acrylamide monomer, which causes the acrylamide monomer and the liquid crystal monomer to crosslink, making it easier to fix the orientation state of the vertically oriented liquid crystal monomer. As a result, the adhesion between the liquid crystal layer 11 and the support layer 12 is improved, the orientation state of the liquid crystal layer 11 is less likely to change over time, and the reliability of the phase difference film 10 is improved. Furthermore, because the liquid crystal layer 11 contains acrylamide monomer, the liquid crystal monomers in the liquid crystal layer 11 become more easily vertically aligned, even if, for example, an alignment film is not provided on the support layer 12. As a result, the process of forming an alignment film is unnecessary in the manufacturing of the phase difference film 10, and the manufacturing of the phase difference film 10 can be simplified.
[0028] The content of acrylamide monomer in the liquid crystal layer 11 is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 5 parts by mass or more and 20 parts by mass or less, when the total polymerizable liquid crystal compound constituting the liquid crystal layer 11 is 100 parts by mass. If the acrylamide monomer content is less than 1 part by mass, the acrylamide monomer may not crosslink well with the liquid crystal monomer, and the orientation characteristics of the liquid crystal layer 11, in which the liquid crystal monomer is vertically oriented, may change over time. As a result, the reliability of the phase difference film tends to decrease. In addition, the adhesion between the liquid crystal layer 11 and the support layer 12 also decreases. If the acrylamide monomer content exceeds 30 parts by mass, the liquid crystal monomer content in the liquid crystal layer 11 becomes relatively low, which may make it difficult to polarize the light incident on the liquid crystal layer 11.
[0029] Furthermore, the liquid crystal layer 11 preferably contains a silane coupling agent in addition to the liquid crystal monomer and the acrylamide monomer. The silane coupling agent is a silicon-containing compound having a hydrolysis group that reacts with an inorganic material and an organic functional group that reacts with an organic material. The inclusion of a silane coupling agent in the liquid crystal layer 11 makes it easier for the liquid crystal monomers to be vertically aligned within the liquid crystal layer 11.
[0030] Examples of silane coupling agents that can be used include amino-based silane coupling agents having an amino group as an organic functional group, silane coupling agents having a (meth)acryloyl group as an organic functional group, mercapto-based silane coupling agents having a mercapto group as an organic functional group, epoxy-based silane coupling agents having an epoxy group as an organic functional group, and sulfide-based silane coupling agents having a sulfide group as an organic functional group. Here, (meth)acryloyl group means acryloyl group or methacryloyl group. A single silane coupling agent may be used alone, or multiple types may be used in combination. In the liquid crystal layer 11 of this embodiment, it is preferable to use an amino-based silane coupling agent having an amino group as an organic functional group among these silane coupling agents. By including an amino-based silane coupling agent in the liquid crystal layer 11, the liquid crystal monomers become more vertically oriented in the liquid crystal layer 11 compared to when other silane coupling agents are used.
[0031] Examples of amino-based silane coupling agents include N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, N-2(aminoethyl)3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane.
[0032] Examples of silane coupling agents having a (meth)acryloyl group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.
[0033] Examples of mercapto-based silane coupling agents include 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane. Examples of epoxy-based silane coupling agents include 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Examples of sulfide-based silane coupling agents include bis[3-(triethoxysilyl)propyl]tetrasulfide.
[0034] When the liquid crystal layer 11 contains a silane coupling agent, the content of the silane coupling agent in the liquid crystal layer 11 is preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 2 parts by mass or more and 10 parts by mass or less, based on 100 parts by mass of the total polymerizable liquid crystal compound constituting the liquid crystal layer 11.
[0035] Furthermore, in this embodiment, when the total polymerizable liquid crystal compound constituting the liquid crystal layer 11 is 100 parts by mass, the content of the material having an amino group is preferably 1 part by mass or more and 35 parts by mass or less, and more preferably 5 parts by mass or more and 25 parts by mass or less. Here, the materials containing amino groups in the liquid crystal layer 11 include acrylamide monomers and amino-based silane coupling agents. By setting the content of the amino group-containing material in the liquid crystal layer 11 within the above range, for example, even when the contact angle of the support layer 12 with respect to the liquid crystal material that forms the basis of the liquid crystal layer 11 is high, the liquid crystal monomers become more likely to be vertically oriented.
[0036] Furthermore, the liquid crystal layer 11 of this embodiment may contain other additives as needed, in addition to the liquid crystal monomer, acrylamide monomer, and silane coupling agent described above. Other additives to be included in the liquid crystal layer 11 are not particularly limited, but examples include photopolymerization initiators and leveling agents. Examples of photopolymerization initiators include 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propane, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane, and 2,2'-dihydroxy-2,2'-dimethyl-1,1'-[methylenebis(4,1-phenylene)]bis(propan-1-one). Commercially available photopolymerization initiators include Irgacure OXE04, Irgacure OXE02, and Irgacure OXE01 from BASF Japan Ltd.
[0037] As leveling agents, fluorine-based leveling agents, acrylic-based leveling agents, and silicone-based leveling agents can be used. Commercially available fluorine-based leveling agents include Megafac R-08, R-30, R-90, F-410, F-411, F-114, F-510, F-551, RS-56, RS-72-K, RS-75, RS-76-E, RS-76-NS, RS-78, RS-90, and DS-21 from DIC Corporation, and Surflon S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, and SA-100 from AGC Seimi Chemical Co., Ltd. Examples of commercially available acrylic leveling agents include BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-356, and BYK-358N, all manufactured by BIC Chemie Japan Co., Ltd. Examples of commercially available silicon-based leveling agents include BYK-300, BYK-302, BYK-306, BYK-307, BYK-310, BYK-313, BYK-315N, BYK-320, BYK-322, BYK-323, BYK-325, and BYK-330 manufactured by BYK-Chemie Japan K.K., and KF-945 and KF-6015, KF-6020 manufactured by Shin-Etsu Chemical Co., Ltd.
[0038] The thickness of the liquid crystal layer 11 is preferably 3 μm or less, more preferably 2 μm or less. On the other hand, the thickness of the liquid crystal layer 11 is preferably 0.3 μm or more, more preferably 0.5 μm or more.
[0039] As described above, the liquid crystal layer 11 is a positive C-plate, and the refractive indices in two directions in the in-plane direction of the liquid crystal layer 11 are defined as n x1 and n y1 , and the refractive index in the thickness direction of the liquid crystal layer 11 is defined as n z1 , the condition n z1 >n x1 =n y1 is satisfied. Here, n x1 means the refractive index in one in-plane direction of the liquid crystal layer 11, and n y1 means the refractive index in the direction orthogonal to the aforementioned one direction of n x1 within the plane of the liquid crystal layer 11. Further, n z1 means the refractive index in the thickness direction of the liquid crystal layer 11. Note that the relationship of refractive indices n x1 =n y1 in the liquid crystal layer 11 does not need to hold strictly, and it is sufficient that they are substantially the same.
[0040] Further, the liquid crystal layer 11 preferably satisfies -50nm<Rth_C(550)<-150nm, where Rth_C(λ) is the phase difference for the wavelength (λ) of light in the thickness direction of the liquid crystal layer 11. The thickness of the liquid crystal layer 11 is calculated from the relationship between the refractive index of the liquid crystal layer 11 and the phase difference Rth_C. When the thickness of the liquid crystal layer 11 is defined as d, in order to achieve the phase difference Rth_C required for the liquid crystal layer 11, Rth_C=((n x1 +ny1 ) / 2-n z1 )×d, the required thickness d of the liquid crystal layer 11 is calculated. When a common liquid crystal material is used, the thickness d of the liquid crystal layer 11 is 0.5 μm or more and 2 μm or less.
[0041] (Support Layer 12) Next, the configuration of the support layer 12 will be described. In the support layer 12 of the present embodiment, the refractive indices in two directions in the in-plane direction of the support layer 12 are defined as n x2 and n y2 , and the refractive index in the thickness direction of the support layer 12 is defined as n z2 , the support layer 12 satisfies n x2 ≧n y2 >n z2 . Here, n x2 means the refractive index in the slow axis direction of the support layer 12, n y2 means the refractive index in the fast axis direction orthogonal to the slow axis of the support layer 12, and n z2 means the refractive index in the thickness direction of the support layer 12. In other words, the support layer 12 is a so-called positive A plate that satisfies the refractive index relationship of n x2 =n y2 >n z2 , or a so-called negative B plate that satisfies the refractive index relationship of n x2 >n y2 >n z2 . Note that the refractive index relationship n x2 =n y2 when the support layer 12 is a positive A plate does not need to be strictly satisfied, and it is sufficient if the values are substantially the same.
[0042] Further, when the in-plane phase difference for the wavelength (λ) of light in the support layer 12 is defined as Re_A(λ), the wavelength dispersion characteristic of the in-plane phase difference Re_A(λ) is preferably from flat dispersion to reverse wavelength dispersion characteristic. The reverse wavelength dispersion characteristic means a characteristic in which the value of the phase difference Re_A(λ) increases as the wavelength of light increases. That is, the support layer 12 preferably has an in-plane phase difference Re_A(λ) that satisfies Re_A(450)<Re_A(550)<Re_A(650). Further, it is preferable that the in-plane retardation Re_A(λ) of the support layer 12 satisfies Re_A(450) / Re_A(550) < 0.9.
[0043] Since the wavelength dispersion characteristic of the in-plane retardation Re_A(λ) of the support layer 12 is a reverse wavelength dispersion characteristic, when the retardation film 10 of the present embodiment is applied to a display device such as the liquid crystal display device 1 (see FIG. 4) described later, light leakage when the display device is viewed from an oblique direction can be reduced. As a result, in the display device including the retardation film 10 of the present embodiment, the contrast ratio when viewed from an oblique direction is improved.
[0044] Further, the support layer 12 preferably satisfies 10 nm < Re_A(550) < 200 nm, where Re_A(λ) is the retardation with respect to the wavelength (λ) of light in the in-plane direction of the support layer 12.
[0045] The support layer 12 can be constituted by, for example, a stretched resin film. The support layer 12 contains at least one resin selected from a cyclo-olefin polymer (COP), triacetylcellulose (TAC), cellulose acetate propionate (CAP), diacetylcellulose, acetylcellulose, and polycarbonate. The support layer 12 may contain these resins alone, but preferably contains a plurality of resins having different wavelength dispersion characteristics of in-plane retardation when formed into a film. Further, among these resins, the support layer 12 preferably contains any one of triacetylcellulose, cellulose acetate propionate, diacetylcellulose, and acetylcellulose, and more preferably contains triacetylcellulose and diacetylcellulose.
[0046] The support layer 12 can control the wavelength dispersion characteristics of the phase difference Re_A(λ) in the in-plane direction of the support layer 12 to a desirable state by adjusting the content ratio of multiple resins with different wavelength dispersion characteristics. More specifically, the support layer 12 can control the wavelength dispersion characteristics of the phase difference Re_A(λ) in the in-plane direction of the support layer 12 to a desirable state by adjusting the content ratio of triacetylcellulose and diacetylcellulose. The ratio of triacetylcellulose to diacetylcellulose in the support layer 12 is preferably in the range of triacetylcellulose:diacetylcellulose = 30:70 to 60:40 by weight.
[0047] Furthermore, the support layer 12 may contain, in addition to the resin, unreacted monomers, which are raw materials for the resin. In addition, the support layer 12 may contain other additives such as dispersants, defoamers, and leveling agents.
[0048] Furthermore, it is preferable that the contact angle of the surface of the support layer 12 on which the liquid crystal layer 11 is laminated with respect to water is between 30° and 60°. If the contact angle of the support layer 12 with respect to water exceeds 60°, when the liquid crystal material is applied to the support layer 12 to form the liquid crystal layer 11, the liquid crystal monomers contained in the liquid crystal layer 11 may not be able to align vertically. On the other hand, if the contact angle of the support layer 12 with respect to water is less than 30°, although this does not affect the vertical orientation of the liquid crystal monomers, the surface treatment required to achieve a support layer 12 with a small contact angle tends to be complicated.
[0049] Furthermore, the thickness of the support layer 12 is preferably 100 μm or less, and more preferably 50 μm or less. On the other hand, the thickness of the support layer 12 is preferably 5 μm or more, and more preferably 10 μm or more.
[0050] Here, the support layer 12 is not limited to a film made of the resin described above, but may be composed of a film containing particles in addition to the resin, for example. Next, other forms of the support layer 12 will be described. Figure 3 is a diagram illustrating another form of the support layer 12, and shows an example of a cross-section of the support layer 12. The support layer 12 shown in Figure 3 includes a resin portion 121 made of a resin and particles 122. Further, similarly to the above-described example, the support layer 12 may contain, in addition to the resin portion 121 and the particles 122, other additives such as unreacted monomers that are raw materials of the resin constituting the resin portion 121, a dispersing agent, an antifoaming agent, and a leveling agent. The resin constituting the resin portion 121 is also the main component of the support layer 12. Therefore, the support layer 12 can also be regarded as having the particles 122 dispersed in the resin portion 121. However, the particles 122 do not have to be dispersed throughout the resin portion 121, and may be partially aggregated. Further, particles 122 that have aggregated to a certain extent may be distributed in the resin portion 121.
[0051] When the support layer 12 includes the resin portion 121 and the particles 122, it becomes possible to control the wavelength dispersion characteristic of the retardation Rth_A(λ) in the thickness direction of the support layer 12. In other words, in the support layer 12, the wavelength dispersion characteristic of the retardation Rth_A(λ) in the thickness direction of the support layer 12 can be controlled by adjusting, for example, the mixing ratio of the resin portion 121 and the particles 122, the refractive index of the particles 122, and the like.
[0052] In the support layer 12 of the present embodiment, the wavelength dispersion characteristics differ between the in-plane retardation Re_A(λ) and the thickness-direction retardation Rth_A(λ). In other words, for example, when the in-plane retardation Re_A(λ) of the support layer 12 has a reverse wavelength dispersion characteristic, the thickness-direction retardation Rth_A(λ) of the support layer 12 has a positive wavelength dispersion characteristic in which the value decreases as the wavelength increases, or a flat wavelength dispersion characteristic in which the value hardly changes as the wavelength increases.
[0053] Furthermore, in the support layer 12 of the present embodiment, it is preferable that the in-plane retardation Re_A(λ) and the thickness-direction retardation Rth_A(λ) satisfy Re_A(450) / Re_A(550) < Rth_A(450) / Rth_A(550).
[0054] As the resin constituting the resin portion 121, at least one of cycloolefin polymer, triacetylcellulose, cellulose acetate propionate, diacetylcellulose, acetylcellulose, and polycarbonate can be used, as in the example described above. Among these, it is preferable to use any of triacetylcellulose, cellulose acetate propionate, diacetylcellulose, or acetylcellulose. These may be used individually or in combination.
[0055] The particles 122 are fine particles, and more preferably nanoparticles. The particle size of the particles 122 is not particularly limited, but can be in the range of 1 nm to 400 nm, for example.
[0056] Particle 122 has a refractive index of n in two directions in the in-plane direction of the support layer 12. x3 and n y3 The refractive index in the thickness direction of the support layer 12 is set to n z3 In that case, n x3 ≥n y3 >n z3 It is preferable that the following conditions be met. Here, n x3 This refers to the refractive index of the particle 122 in the slow phase axis direction of the support layer 12, and n y3 This refers to the refractive index of the particle 122 in the phase-advancing axis direction perpendicular to the slow phase axis of the support layer 12, where n z3 This refers to the refractive index of the particles 122 in the thickness direction of the support layer 12. Furthermore, it is preferable that the particles 122 satisfy the condition Rth_P(450)>Rth_P(550)>Rth_P(650) when Rth_P(λ) is the phase difference with respect to the wavelength of light λ (nm) in the thickness direction of the support layer 12.
[0057] For particle 122, for example, smectite can be used. Other minerals that can be used include, for example, minerals of the smectite group. Specifically, these include hectorite, montmorillonite, and bentonite. Also, minerals of the kaolinite group such as kaolinite and antigonite, and minerals of the mica group such as mica can be used. In this embodiment, organic smectite obtained by artificial synthesis can be particularly preferably used as particle 122. Examples of organic smectite include dimethylstearylammonium heclite. Other examples of organic smectite include lithium sodium magnesium silicate trioctylmethylammonium. Furthermore, examples of organic smectite include lithium sodium magnesium silicate polyoxyethylene coconut alkylmethylammonium chloride.
[0058] The mixing ratio of the resin portion 121 and the particles 122 in the support layer 12 is preferably in the range of resin:particles = 95:5 to 70:30 by weight. By setting the range in this manner, it becomes easier to control the wavelength dispersion characteristics of the phase difference Rth_A(λ) in the thickness direction of the support layer 12.
[0059] <Method for manufacturing phase difference film 10> Next, the manufacturing method for the phase difference film 10 will be described. When manufacturing the phase difference film 10, first, the liquid crystal material that will serve as the basis for the polymerizable liquid crystal compound constituting the liquid crystal layer 11 is prepared.
[0060] The liquid crystal material comprises the liquid crystal monomer and acrylamide monomer described above. The liquid crystal material may also contain the various additives described above, as needed. The liquid crystal material preferably contains a silane coupling agent as an additive, and more preferably contains a silane coupling agent having an amino group.
[0061] Furthermore, in this embodiment, when the liquid crystal material is 100 parts by mass, the content of the material having an amino group is preferably 1 part by mass or more and 30 parts by mass or less, and more preferably 5 parts by mass or more and 20 parts by mass or less. As mentioned above, examples of materials having an amino group include acrylamide monomers and amino-based silane coupling agents. By setting the content of the amino group-containing material in the liquid crystal material to the above range, for example, even when using a support layer 12 with a high contact angle with the liquid crystal material, the liquid crystal monomers become more likely to be vertically oriented.
[0062] Liquid crystal materials are used in a dispersed state in a solvent. The solvent is not particularly limited as long as it can uniformly disperse the liquid crystal monomer and acrylamide monomer contained in the liquid crystal material, and any known solvent can be used. Examples of solvents include acetone, toluene, xylene, benzene, cyclohexane, hexane, methyl acetate, ethyl acetate, butyl acetate, isopropyl acetate, propyl acetate, methyl isobutyl ketone, methyl ethyl ketone, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, cyclohexanone, and cyclopentanone.
[0063] Next, the liquid crystal material is applied onto the support layer 12. Figure 4 is a diagram illustrating an example of a manufacturing method for the phase difference film 10 (see Figure 1) of this embodiment, and shows a coating apparatus 500 used in the manufacture of the phase difference film 10. Figure 4 shows the state in which the liquid crystal material, which is the material for the liquid crystal layer 11, is being applied to the film-like support layer 12 using the coating apparatus 500.
[0064] The coating apparatus 500 includes a supply unit 510 that unwinds and supplies the support layer 12 wound in a roll shape, and a recovery unit 520 that winds and recovers the phase difference film 10 obtained by forming the liquid crystal layer 11 on the support layer 12. The coating apparatus 500 also includes a plurality of transport rolls 530 that support the support layer 12 from the back side and transport the support layer 12 in the direction of arrow A. The coating apparatus 500 also includes a coating unit 540 that applies liquid crystal material, which is the material for the liquid crystal layer 11, to the surface of the support layer 12 transported by the transport rolls 530. The coating apparatus 500 also includes a heating unit 550 that heats the liquid crystal material applied on the support layer 12. The coating apparatus 500 also includes an irradiation unit 560 that irradiates the liquid crystal material that has passed through the heating unit 550 with ultraviolet light, which is an example of active radiation.
[0065] In the coating apparatus 500, the liquid crystal material is applied to the surface of the support layer 12, which is supplied from the supply unit 510 and conveyed by the conveyor roll 530, by the coating unit 540. The coating unit 540 shown in Figure 4 is a so-called slot die coater that applies the liquid crystal material held in the tank 541 onto the support layer 12 using a slot die 542. Furthermore, the method of applying the liquid crystal material by the coating section 540 is not particularly limited, and known methods such as die coating, spin coating, gravure coating, spray coating, and roll coating can be applied.
[0066] Next, the liquid crystal material applied to the support layer 12 is heated and dried. Specifically, the liquid crystal material coated on the support layer 12 is heated by the heating unit 550. This causes the solvent contained in the liquid crystal material to evaporate, and the liquid crystal material dries. Furthermore, heating and drying the liquid crystal material causes the liquid crystal monomers contained in the liquid crystal material to become vertically oriented. In this embodiment, as described above, the liquid crystal material contains acrylamide monomer. This makes it possible to vertically align the liquid crystal monomer even when the liquid crystal material is applied directly onto the support layer 12 without, for example, an alignment film.
[0067] The heating temperature of the liquid crystal material by the heating unit 550 can be, for example, between 40°C and 100°C. The heating time of the liquid crystal material by the heating unit 550 can be, for example, between 30 seconds and 300 seconds. Furthermore, it is preferable to adjust the heating temperature and heating time of the liquid crystal material by the heating unit 550 according to the type of liquid crystal monomer contained in the liquid crystal material.
[0068] Next, the liquid crystal monomers contained in the liquid crystal material coated on the support layer 12 are polymerized to obtain a liquid crystal layer 11 made of a polymerizable liquid crystal compound. Specifically, the liquid crystal material coated on the support layer 12 is irradiated with active radiation (ultraviolet light in this example) by the irradiation unit 560. As a result, the liquid crystal monomers contained in the liquid crystal material polymerize, and the orientation characteristics of the vertically oriented liquid crystal monomers are fixed by the polymerization of the liquid crystal monomers. As a result, a liquid crystal layer 11 made of a polymerizable liquid crystal compound is formed on the support layer 12, and the phase difference film 10 of this embodiment is obtained by laminating the liquid crystal layer 11 and the support layer 12. The wavelength of ultraviolet light irradiated onto the liquid crystal material by the irradiation unit 560 varies depending on the type of liquid crystal monomer contained in the liquid crystal material, but can be, for example, 300 nm to 400 nm.
[0069] Subsequently, the obtained phase difference film 10 is recovered by the recovery unit 520, being wound into a roll shape with the liquid crystal layer 11 facing inward.
[0070] <Description of Liquid Crystal Display Device 1> The phase difference film 10 of this embodiment can be applied to a liquid crystal display device 1, for example, as an example of a display device that displays an image. Figure 5 is a diagram illustrating a liquid crystal display device 1 to which the phase difference film 10 of this embodiment is applied, and shows an example of the cross-sectional structure of the liquid crystal display device 1.
[0071] The liquid crystal display device 1 displays images using the IPS (In-Plane-Switching) method. The liquid crystal display device 1 comprises a backlight 20 and a liquid crystal panel 30. The backlight 20 is located on the back side of the liquid crystal panel 30, as viewed by the user viewing the liquid crystal display device 1. The liquid crystal display device 1 displays images by modulating the light emitted from the backlight 20 using the liquid crystal panel 30.
[0072] The backlight 20 illuminates the liquid crystal panel 30 with light. The backlight 20 may be edge-lit or direct-lit. For example, a cold cathode fluorescent lamp or a white LED (Light Emitting Diode) can be used as the backlight 20, but it is not limited to these.
[0073] The liquid crystal panel 30 is constructed by sequentially laminating a first linear polarizing plate 40, a liquid crystal cell 50, a phase difference film 10, and a second linear polarizing plate 60 from the backlight 20 side. In the liquid crystal panel 30, the phase difference film 10 is laminated such that the liquid crystal layer 11 faces the liquid crystal cell 50 and the support layer 12 faces the second linear polarizing plate 60. In this embodiment, the second linear polarizing plate 60 is an example of a polarizing member, and the laminated structure of the phase difference film 10 and the second linear polarizing plate 60 is an example of an optical member.
[0074] The first linear polarizing plate 40 comprises a polarizer 41 and protective layers 42 and 43 laminated on one side (the side facing the backlight 20) and the other side (the side facing the liquid crystal cell 50) of the polarizer 41. Furthermore, the second linear polarizing plate 60 comprises a polarizer 61 and a protective layer 62 laminated on the side of the polarizer 61 opposite to the phase difference film 10. Note that no protective layer is provided on the side of the polarizer 61 facing the phase difference film 10. In the liquid crystal panel 30 of this embodiment, the phase difference film 10 also serves as the protective layer for the polarizer 61.
[0075] The polarizer 41 of the first linear polarizer 40 and the polarizer 61 of the second linear polarizer 60 are arranged so that their absorption axis directions are perpendicular to each other. As polarizers 41 and 61, for example, a resin film can be used in which iodine compound molecules are impregnated into a film made of polyvinyl alcohol (PVA) and then uniaxially stretched.
[0076] For example, a film made of resin can be used as the protective layers 42 and 43 of the first linear polarizing plate 40 and the protective layer 62 of the second linear polarizing plate 60. Examples of resins include, but are not limited to, triacetylcellulose (TAC) and polyethylene terephthalate (PET). For the protective layer 43, it is preferable that the phase difference in the in-plane direction and the phase difference in the thickness direction are 0 or close to 0 in order to perform optical compensation for the IPS type liquid crystal display device 1.
[0077] As described above, the liquid crystal cell 50 is an IPS-type liquid crystal cell, and has a cell structure in which liquid crystal is sandwiched between two substrates, for example, made of glass. Power is supplied to the liquid crystal cell 50 by a power supply (not shown), and the light transmission state is controlled by the horizontal rotation of the liquid crystal along the in-plane direction of the liquid crystal cell 50. For the liquid crystal used in this IPS (In-Plane-Switching) liquid crystal cell, either a so-called positive-type liquid crystal, where the dielectric anisotropy is along the molecular long axis, or a so-called negative-type liquid crystal, where the dielectric anisotropy is along the molecular short axis, may be applied. Furthermore, the electrode structure may be either the IPS (In-Plane-Switching) method or the FFS (Fringe-Field Switching) method, a so-called striped electric field method, and is applicable to liquid crystal orientations where the liquid crystal is oriented uniaxially in the horizontal direction of the cell, either in the absence of an electric field or with an applied electric field.
[0078] In this embodiment, the liquid crystal display device 1 has a second linear polarizing plate 60, which is an example of a polarizing member, a support layer 12, and a liquid crystal layer 11 stacked in this order. The slow-speed axis of the support layer 12 in the phase difference film 10 and the absorption axis of the polarizer 61 in the second linear polarizing plate 60 stacked on the phase difference film 10 are arranged orthogonally.
[0079] The liquid crystal display device 1 includes a phase difference film 10 having a liquid crystal layer 11 and a support layer 12. By including this film, when the liquid crystal cell 50 is set to display black, the amount of light leakage when viewing the liquid crystal display device 1 from an oblique direction can be reduced. As a result, the liquid crystal display device 1 equipped with the phase difference film 10 of this embodiment has an improved contrast ratio when viewed from an oblique direction.
[0080] In the liquid crystal display device 1 shown in Figure 5, the phase difference film 10 is laminated on the side opposite to the backlight 20 relative to the liquid crystal cell 50, but this is not the only configuration. The phase difference film 10 may also be laminated on the side of the backlight 20 relative to the liquid crystal cell 50. Furthermore, in the liquid crystal display device 1 shown in Figure 5, the phase difference film 10 is arranged such that the support layer 12 is on the second linear polarizing plate 60 (polarizer 61) side and the liquid crystal layer 11 is on the liquid crystal cell 50 side, but it is not limited to this. The phase difference film 10 may also be arranged such that the liquid crystal layer 11 is on the second linear polarizing plate 60 side and the support layer 12 is on the liquid crystal cell side 50. In addition, the second linear polarizing plate 60, which is an example of a polarizing member, the liquid crystal layer 11, and the support layer 12 may be stacked in this order. In this case, the absorption axis of the polarizer 61 in the second linear polarizing plate 60 and the slow axis of the support layer 12 are arranged in parallel.
[0081] <Configuration of Organic EL Display Device 2> The phase difference film 10 of this embodiment can be applied not only to the liquid crystal display device 1 described above, but also to an organic EL display device 2, which is an example of a light-emitting display device. Figure 6 is a diagram illustrating an organic EL display device 2 to which the phase difference film 10 of this embodiment is applied, and shows an example of the cross-sectional structure of the organic EL display device 2.
[0082] The organic EL display device 2 comprises an organic EL display 70 including an organic EL light-emitting element, a phase difference film 10 laminated on the surface of the organic EL display 70, and a linear polarizing plate 80 laminated on the surface of the phase difference film 10. In the organic EL display device 2, the phase difference film 10 is laminated such that the liquid crystal layer 11 faces the organic EL display and the support layer 12 faces the linear polarizing plate 80. In this embodiment, the linear polarizing plate 80 is an example of a polarizing member, and the laminated structure of the phase difference film 10 and the linear polarizing plate 80 is an example of an optical member. The linear polarizing plate 80 has a structure in which a polarizer 81 and a protective layer 82 are laminated, similar to the second linear polarizing plate 60 in the liquid crystal display device 1 described above. In the organic EL display device 2, power is supplied by a power supply (not shown), the organic EL display 70 emits light, and an image is displayed.
[0083] In the organic EL display device 2 of this embodiment, the angle between the slow axis of the support layer 12 in the phase difference film 10 and the absorption axis of the polarizer 81 in the linear polarizing plate 80 laminated on the phase difference film 10 is preferably 40° or more and 50° or less, and more preferably 45°. The angle between the slow axis of the support layer 12 and the absorption axis of the polarizer 81 has the above-described relationship, so that the laminated structure of the phase difference film 10 and the linear polarizer 80 becomes a circular polarizer. As a result, ambient light incident on the organic EL display device 2 is cut off by the laminated structure of the phase difference film 10 and the linear polarizer 80, making it possible to suppress the reflection of ambient light in the organic EL display device 2. In addition, the laminated structure of the phase difference film 10 and the linear polarizer 80 acts as an anti-reflective film for the organic EL display device 2. [Examples]
[0084] Next, the present invention will be described in more detail using examples. However, the present invention is not limited to the following examples unless it exceeds the scope of its essence.
[0085] [Example 1] (Preparation of liquid crystal materials) A liquid crystal material consisting of 7 parts by mass of liquid crystal monomer of formula (I), 13 parts by mass of liquid crystal monomer of formula (II), 2 parts by mass of acrylamide monomer, and 0.5 parts by mass of a photopolymerization initiator (product name: Omnirad907, manufactured by GM Resins BV) was dissolved in 78 parts by mass of propylene glycol methyl ether acetate, a solvent, to prepare a coating solution containing the liquid crystal material.
[0086] [ka]
[0087] (Preparation of support layer 12) A film made of COP with a thickness of 30 μm was prepared as the support layer 12.
[0088] (Preparation of phase difference film 10) A coating solution containing liquid crystal material was applied onto a support layer 12 using a slot die coater, and then heated and dried at 80°C for 3 minutes to orient the liquid crystal monomers vertically. Subsequently, the liquid crystal monomers were polymerized by irradiating them with ultraviolet light at a wavelength of 365 nm for 30 seconds to form a 1.2 μm thick liquid crystal layer 11 made of polymerizable liquid crystal compound, thereby obtaining a phase difference film 10. The phase difference Rth(550) in the thickness direction of the obtained phase difference film 10 was -140 nm.
[0089] [Comparative Example 1] A phase difference film 10 was obtained in the same manner as in Example 1, except that a liquid crystal material was used that did not contain acrylamide monomer and contained 2 parts by mass of 3-aminopropyltrimethoxysilane as a silane coupling agent. The phase difference Rth(550) in the thickness direction of the obtained phase difference film 10 was -135 nm.
[0090] [Comparative Example 2] A phase difference film 10 was obtained in the same manner as in Example 1, except that a liquid crystal material that does not contain acrylamide monomer was used. In the resulting phase difference film 10, the liquid crystal monomers did not align vertically, making it impossible to measure the phase difference Rth(550) in the thickness direction.
[0091] [evaluation] (Evaluation of adhesion) The adhesion properties of the phase difference films 10 of Example 1 and Comparative Example 1 were evaluated by a cross-cut test. First, 11 cuts were made on the surface of the phase difference film 10 facing the liquid crystal layer 11 using a utility knife, creating 100 grid squares. A cutter guide was used when making the cuts, and the interval between cuts was 1 mm. Subsequently, cellophane tape (registered trademark) was firmly pressed onto the grid area, and the end of the cellophane tape was quickly peeled off at a 45° angle. The condition of the grid was then visually observed and evaluated.
[0092] As a result of the above test, in the phase difference film 10 of Example 1, all 100 grid-like films remained intact, confirming that the adhesion between the liquid crystal layer 11 and the support layer 12 was high. On the other hand, in the phase difference film 10 of Comparative Example 1, all 100 grid-like film segments peeled off, confirming that the adhesion between the liquid crystal layer 11 and the support layer 12 was insufficient.
[0093] (Reliability assessment) The reliability of the phase difference films 10 of Example 1 and Comparative Example 1 was evaluated by the following method. The phase difference film 10 was placed in a constant temperature and humidity chamber at 85°C and 85% humidity and held for 200 hours. The phase difference Rth in the thickness direction of the phase difference film 10 was then compared before and after the test (before and after being placed in the constant temperature and humidity chamber).
[0094] In the phase difference film 10 of Example 1, the change in the phase difference Rth in the thickness direction before and after the test was 2% or less, indicating almost no change. This confirmed that the phase difference film 10 of Example 1 is less susceptible to quality changes over time and is highly reliable. In contrast, in the phase difference film 10 of Comparative Example 1, the phase difference Rth in the thickness direction after the test was 15% lower than before the test, confirming its low reliability.
[0095] Next, phase difference films 10 with different content ratios of amino group-containing material in the liquid crystal layer 11 were fabricated and evaluated. [Example 2] A liquid crystal material consisting of 7 parts by mass of the liquid crystal monomer of formula (I), 13 parts by mass of the liquid crystal monomer of formula (II), 0.2 parts by mass of acrylamide monomer, 0.2 parts by mass of 3-aminopropyltrimethoxysilane, a silane coupling agent having an amino group, and 0.5 parts by mass of a photopolymerization initiator (trade name: Omnirad907, manufactured by GM Resins BV) was dissolved in 79.1 parts by mass of propylene glycol methyl ether acetate, a solvent, to prepare a coating solution containing the liquid crystal material. The content of the material having an amino group relative to the total amount of liquid crystal material was 2% by mass. Using the prepared coating solution, a phase difference film 10 was obtained in the same manner as in Example 1.
[0096] [Example 3] A liquid crystal material containing 6 parts by mass of the liquid crystal monomer of formula (I), 14 parts by mass of the liquid crystal monomer of formula (II), 1 part by mass of acrylamide monomer, 1 part by mass of 3-aminopropyltrimethoxysilane, a silane coupling agent having an amino group, and 0.5 parts by mass of a photopolymerization initiator (trade name: Omnirad907, manufactured by GM Resins BV) was dissolved in 77.5 parts by mass of propylene glycol methyl ether acetate, a solvent, to prepare a coating solution containing the liquid crystal material. The content of the material having an amino group relative to the total amount of the liquid crystal material was 9% by mass. Using the prepared coating solution, a phase difference film 10 was obtained in the same manner as in Example 1.
[0097] [Example 4] A liquid crystal material containing 5 parts by mass of the liquid crystal monomer of formula (I), 15 parts by mass of the liquid crystal monomer of formula (II), 2 parts by mass of the acrylamide monomer, 1 part by mass of N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, a silane coupling agent having an amino group, and 0.5 parts by mass of a photopolymerization initiator (trade name: Omnirad907, manufactured by GM Resins BV) was dissolved in 76.5 parts by mass of propylene glycol monomethyl ether, a solvent, to prepare a coating solution containing the liquid crystal material. The content of the material having an amino group relative to the total amount of the liquid crystal material was 13% by mass. Using the prepared coating solution, a phase difference film 10 was obtained in the same manner as in Example 1.
[0098] [Example 5] A liquid crystal material containing 5 parts by mass of the liquid crystal monomer of formula (I), 15 parts by mass of the liquid crystal monomer of formula (II), 3.5 parts by mass of acrylamide monomer, 3 parts by mass of N-2(aminoethyl)3-aminopropylmethyldimethoxysilane, a silane coupling agent having an amino group, and 0.5 parts by mass of a photopolymerization initiator (trade name: Omnirad907, manufactured by GM Resins BV) was dissolved in 73.0 parts by mass of propylene glycol monomethyl ether, a solvent, to prepare a coating solution containing the liquid crystal material. The content of the material having an amino group relative to the total amount of the liquid crystal material was 24% by mass. Using the prepared coating solution, a phase difference film 10 was obtained in the same manner as in Example 1.
[0099] [evaluation] (Evaluation of orientation) The phase difference films 10 obtained in Examples 2 to 5 were observed, and the orientation state of the liquid crystal monomers in the liquid crystal layer 11 was evaluated. In addition, the phase difference Rth(550) in the thickness direction of the phase difference films 10 obtained in Examples 2 to 5 was measured. Table 1 shows the measurement results of the phase difference Rth(550) in the thickness direction of the phase film 10 obtained in Examples 2 to 5, as well as the results of visual evaluation.
[0100] [Table 1]
[0101] In all of the phase difference films 10 of Examples 2 to 5, the liquid crystal monomers were vertically oriented. Therefore, it was confirmed that by preparing the liquid crystal layer 11 using a liquid crystal material in which the content of the amino group material is 1% by mass or more and 30% by mass or less, the liquid crystal monomers in the liquid crystal layer 11 are vertically oriented.
[0102] Furthermore, when comparing the phase difference films 10 obtained in Examples 2 to 5, the phase difference film 10 of Example 2, which used a liquid crystal material with an amino group content of 2% by mass, showed cloudiness in the liquid crystal layer 11 compared to the phase difference films 10 of Examples 3 and 4. In addition, the phase difference film 10 of Example 5, which used a liquid crystal material with an amino group content of 24% by mass, showed lower orientation of liquid crystal monomers and a smaller value of phase difference Rth in the thickness direction compared to the phase difference films 10 of Examples 3 and 4. This confirmed that it is more preferable to produce the liquid crystal layer 11 using a liquid crystal material with an amino group content of 5% by mass or more and 20% by mass or less.
[0103] Next, a phase difference film 10 was fabricated using a support layer 12 in which the wavelength dispersion characteristics of the phase difference Re_A(λ) in the in-plane direction were inverse wavelength dispersion characteristics, and the film was evaluated. [Example 6] (Preparation of support layer 12) A support layer 12 consisting of a 70 μm thick film was prepared using a resin containing triacetylcellulose and diacetylcellulose in a ratio of triacetylcellulose:diacetylcellulose = 70:30.
[0104] (Preparation of phase difference film 10) A coating solution containing a liquid crystal material was prepared in the same manner as in Example 1. A coating solution containing liquid crystal material was applied onto a support layer 12 using a slot die coater, and then heated and dried at 80°C for 3 minutes to orient the liquid crystal monomers vertically. Subsequently, the liquid crystal monomers were polymerized by irradiating them with ultraviolet light at a wavelength of 365 nm for 30 seconds to form a 1.2 μm thick liquid crystal layer 11 made of polymerizable liquid crystal compound, thereby obtaining a phase difference film 10.
[0105] [evaluation] (Evaluation of contrast ratio) The phase difference film 10 obtained in Example 6 was applied to the IPS-type liquid crystal display device 1, and the contrast ratio was evaluated. First, a second linear polarizing plate 60 was prepared, consisting of a 20 μm thick polyvinyl alcohol-based polarizer 61 and a 30 μm thick protective layer 62 made of triacetylcellulose. The second linear polarizing plate 60 was then laminated onto the support 12 side of the phase difference film 10, with the polarizer 61 facing the phase difference film 10, to obtain an optical component consisting of the phase difference film 10 and the second linear polarizing plate 60. This optical component, consisting of the phase difference film 10 and the second linear polarizing plate 60, was then attached to the surface of an IPS-type monitor liquid crystal cell 50 using an adhesive, with the phase difference film 10 facing the liquid crystal cell 50, to obtain a liquid crystal display device 1 having the laminated structure shown in Figure 5.
[0106] Then, for both the case where the liquid crystal cell 50 was set to display white and the case where the liquid crystal cell 50 was set to display black, the brightness of the liquid crystal display device 1 was measured while varying the elevation angle from -80° to 80° at an azimuth angle of 45°. Note that the elevation angle refers to the angle of inclination with respect to the direction perpendicular to the surface of the liquid crystal display device 1 (phase difference film 10) (normal direction). In addition, an elevation angle of 0° is the normal direction of the liquid crystal display device 1. Furthermore, an elevation angle of 80° is the direction tilted 80° from the normal direction of the liquid crystal display device 1 towards the azimuth angle of 45°, and an elevation angle of -80° is the direction tilted 80° from the normal direction of the liquid crystal display device 1 in the opposite direction to the azimuth angle of 45° (azimuth angle of 225°).
[0107] Furthermore, as Comparative Example 3, the brightness of the liquid crystal display device 1 was measured in the same manner for a liquid crystal display device 1 without the phase difference film 10 and the second linear polarizing plate 60 attached, both when the liquid crystal cell 50 was set to display white and when the liquid crystal cell 50 was set to display black. In the following, the brightness of the liquid crystal display device 1 when the liquid crystal cell 50 is set to display white will be referred to as the white display brightness, and the brightness of the liquid crystal display device 1 when the liquid crystal cell 50 is set to display black will be referred to as the black display brightness.
[0108] Figures 7(a) and 7(b) show the measurement results of the brightness of the liquid crystal display device 1. Figure 7(a) shows the measurement results of the brightness of the white display, and Figure 7(b) shows the measurement results of the brightness of the black display. Table 1 also shows the measurement results for white display brightness and black display brightness at an elevation angle of 60°, as well as the ratio of white display brightness to black display brightness (contrast ratio CR) at an elevation angle of 60°, for Example 6 and Comparative Example 3. The contrast ratio CR is calculated as (white display brightness) / (black display brightness).
[0109] [Table 2]
[0110] As shown in Figure 7(b), in the liquid crystal display device 1 of Comparative Example 3, which does not have the phase difference film 10, the black display brightness increases as the absolute value of the elevation angle increases, and when the liquid crystal display device 1 is viewed from an oblique direction, light loss occurs from the backlight 20. In contrast, in the liquid crystal display device 1 of Example 6, to which the phase difference film 10 of this embodiment is applied, the increase in black display brightness is suppressed even when the absolute value of the elevation angle increases. Therefore, it was confirmed that by applying the phase difference film 10 of this embodiment, light loss when the liquid crystal display device 1 is viewed from an oblique direction is reduced.
[0111] Furthermore, the contrast ratio at an elevation angle of 60° was 6.6 times greater in Example 6 compared to the contrast ratio in Comparative Example 3. Therefore, it was confirmed that applying the phase difference film 10 of this embodiment improves the contrast performance of the liquid crystal display device 1.
[0112] [Example 7] A phase difference film 10 was obtained in the same manner as in Example 3, except that a stretched COP film (product name: ZF-35, manufactured by Japan ZEON Co., Ltd.) was used as the support layer 12. Then, the obtained phase difference film 10 was applied to the liquid crystal display device 1 in the same manner as in Example 6, and the contrast ratio was evaluated. Specifically, similar to Example 6, the second linear polarizing plate 60 was laminated on the support 12 side of the phase difference film 10 so that the polarizer 61 was on the phase difference film 10 side, thereby obtaining an optical component consisting of the phase difference film 10 and the second linear polarizing plate 60. This optical component was then attached to the surface of a liquid crystal cell 50 for a TV using an adhesive so that the phase difference film 10 was on the liquid crystal cell 50 side, resulting in a liquid crystal display device 1 having the laminated structure shown in Figure 5.
[0113] Then, for both the case where the liquid crystal cell 50 displays white and the case where the liquid crystal cell 50 displays black, the brightness of the liquid crystal display device 1 was measured while varying the elevation angle from -80° to 80° at an azimuth angle of 45°. Furthermore, as Comparative Example 4, the brightness of the liquid crystal display device 1 without the phase difference film 10 was measured in the same manner, both when the liquid crystal cell 50 was displaying white and when the liquid crystal cell 50 was displaying black.
[0114] Figures 8(a) and 8(b) show the measurement results of the brightness of the liquid crystal display device 1. Figure 8(a) shows the measurement results of the brightness of the white display, and Figure 8(b) shows the measurement results of the brightness of the black display. Note that in Figures 8(a) and 8(b), the brightness is normalized so that the brightness at an elevation angle of 0° is 1. Table 3 also shows the measurement results for white display brightness and black display brightness at the front and at an elevation angle of 60°, as well as the ratio of white display brightness to black display brightness (contrast ratio CR) at the front and at an elevation angle of 60°, for Example 7 and Comparative Example 4.
[0115] [Table 3]
[0116] As shown in Figure 8(b), similar to Comparative Example 3, in the liquid crystal display device 1 of Comparative Example 4, which does not have the phase difference film 10, the black display brightness increases as the absolute value of the elevation angle increases, and when the liquid crystal display device 1 is viewed from an oblique direction, light loss occurs from the backlight 20. In contrast, in the liquid crystal display device 1 of Example 7, to which the phase difference film 10 of this embodiment is applied, the increase in black display brightness is suppressed even when the absolute value of the elevation angle increases. Therefore, it was confirmed that by applying the phase difference film 10 of this embodiment, light loss when the liquid crystal display device 1 is viewed from an oblique direction is reduced.
[0117] Furthermore, the contrast ratio at an elevation angle of 60° was 11 times greater in Example 7 than in Comparative Example 4. Therefore, it was confirmed that applying the phase difference film 10 of this embodiment improves the contrast of the liquid crystal display device 1. [Explanation of Symbols]
[0118] 1…Liquid crystal display device, 2…Organic EL display device, 10…Phase difference film, 11…Liquid crystal layer, 12…Support layer, 20…Backlight, 30…Liquid crystal panel, 40…First linear polarizer, 50…Liquid crystal cell, 60…Second linear polarizer, 70…Organic EL display, 80…Linear polarizer
Claims
1. A liquid crystal material for forming polymerizable liquid crystal compounds, Liquid crystal monomer and It contains acrylamide monomer, The liquid crystal monomer includes at least one first liquid crystal monomer having reactive groups at both ends of the molecule, and at least one second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end. Liquid crystal materials.
2. Furthermore, the liquid crystal material according to claim 1, further comprising a silane coupling agent.
3. The silane coupling agent is the liquid crystal material according to claim 2, having an amino group.
4. The liquid crystal material according to claim 1, which does not contain any monomers other than the liquid crystal monomer and the acrylamide monomer.
5. The liquid crystal material according to claim 1, wherein the liquid crystal monomer contains a larger amount of the first liquid crystal monomer compared to the second liquid crystal monomer.
6. The liquid crystal material according to any one of claims 1 to 3, wherein, when the total amount of the liquid crystal material is 100 parts by mass, the content of the material having an amino group is 1 part by mass or more and 30 parts by mass or less.
7. Supporting layer and A liquid crystal layer is formed by coating a liquid crystal material containing a first liquid crystal monomer having reactive groups at both ends of the molecule, a second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end, and an acrylamide monomer onto the support layer and polymerizing it, thereby forming a polymerizable liquid crystal compound. A laminate comprising the following features.
8. The laminate according to claim 7, wherein the support layer has a contact angle with water of 30° or more and 60° or less.
9. The laminate according to claim 7, wherein the liquid crystal layer is a positive C plate in which the liquid crystal monomers are vertically oriented, and when the phase difference with respect to the wavelength of light λ (nm) in the thickness direction of the liquid crystal layer is Rth_C(λ), the laminate satisfies -50 nm < Rth_C(550) < -150 nm.
10. The support layer has a refractive index in two directions in the in-plane direction of the support layer, n x2 and n y2 The refractive index in the thickness direction of the support layer is n z2 In that case, n x2 ≥n y2 >n z2 Satisfying the conditions, The laminate according to claim 7, wherein the liquid crystal layer is a positive C plate in which the liquid crystal monomers are crosslinked in a vertically oriented state, and is directly laminated on the support layer.
11. The laminate according to claim 10, wherein the support layer satisfies the condition that 10 nm < Re_A(550) < 200 nm when Re_A(λ) is the phase difference with respect to the wavelength λ (nm) of light in the in-plane direction of the support layer.
12. The laminate according to claim 10, wherein the support layer satisfies the following conditions: Re_A(450) < Re_A(550) < Re_A(650), where Re_A(λ) is the phase difference with respect to the wavelength λ (nm) of light in the in-plane direction of the support layer.
13. The laminate according to claim 10, wherein the support layer comprises at least one of diacetylcellulose, triacetylcellulose, cellulose acetate butyrate, cellulose acetate propionate, cycloolefin, and polycarbonate as the resin.
14. The laminate according to claim 13, wherein the support layer comprises a plurality of types of resins having different wavelength dispersion characteristics.
15. The laminate according to claim 10, wherein the support layer comprises a resin and particles.
16. The laminate according to claim 15, wherein the particles include smectite.
17. The particles have refractive indices in two directions in the in-plane direction of the support layer denoted as n x3 and n y3 and a refractive index in the thickness direction of the support layer denoted as n z3 , then n x3 ≧n y3 >n z3 The laminate according to claim 15, which satisfies the above relationship.
18. The laminate according to claim 15, wherein the particles satisfy Rth_P(450) > Rth_P(550) > Rth_P(650) when Rth_P(λ) is the phase difference with respect to the wavelength of light λ (nm) in the thickness direction of the support layer.
19. The laminate according to claim 10, wherein the wavelength dispersion characteristics of the phase difference in the in-plane direction of the support layer are different from the wavelength dispersion characteristics of the phase difference in the thickness direction of the support layer.
20. The laminate according to claim 19, wherein the support layer satisfies the following condition: Re_A(450) / Re_A(550) < Rth_A(450) / Rth_A(550), where Re_A(λ) is the phase difference with respect to the wavelength λ (nm) of light in the in-plane direction of the support layer, and Rth_A(λ) is the phase difference with respect to the wavelength λ (nm) of light in the thickness direction of the support layer.
21. A polarizing member that polarizes light, The polarizing member comprises a phase difference film laminated on the polarizing member, The phase difference film is an optical member comprising a laminate as described in any one of claims 7 to 20.
22. The support layer in the laminate has a refractive index in two directions in the in-plane direction of the support layer, n x2 and n y2 The refractive index in the thickness direction of the support layer is n z2 In that case, n x2 ≥n y2 >n z2 Satisfying the conditions, When the polarizing member, the support layer, and the liquid crystal layer are stacked in this order, the absorption axis of the polarizing member and the slow axis of the support layer are arranged orthogonally. The optical member according to claim 21, wherein when the polarizing member, the liquid crystal layer, and the support layer are stacked in this order, the absorption axis of the polarizing member and the slow axis of the support layer are arranged in parallel.
23. A liquid crystal cell that controls the light transmission state, The optical member according to claim 21 laminated on the liquid crystal cell and A display device equipped with the following features.
24. An organic EL layer containing organic EL light-emitting diodes, The optical member according to claim 21, which is laminated on the organic EL layer. A display device equipped with the following features.
25. The display device according to claim 24, wherein the angle between the absorption axis of the polarizing member and the slow axis of the support layer is 40° or more and 50° or less.
26. A step of coating a support layer with a liquid crystal material in which a liquid crystal monomer containing at least one first liquid crystal monomer having reactive groups at both ends of the molecule, and at least one second liquid crystal monomer having a reactive group at one end of the molecule and a cyano group at the other end, and an acrylamide monomer dispersed in a solvent, A step of vertically aligning the liquid crystal monomer by evaporating the solvent from the liquid crystal material, A step of polymerizing the liquid crystal material to form a liquid crystal layer consisting of a polymerizable liquid crystal compound in which the liquid crystal monomers are vertically oriented. A method for manufacturing a laminate containing a laminate.
Citation Information
Patent Citations
Production method for micro-retarder without alignment layer
CN102243330A
Retardation film and liquid crystal display using the same
JP2003315539A
Polymerizable liquid crystal composition and polymer thereof
JP2007016213A
Layered product, liquid crystal panel, and liquid crystal display device
JP2008158310A
Optically-compensatory film, polarizing plate, liquid crystal display device, and method for producing optically-compensatory film
JP2016006439A